Solvent-free synthesis of acetylated cashew gum for oral delivery system of insulin. (1st March 2019) - Vasconcelos Silva, Eliadna de Lemos; Oliveira, Antônia Carla de Jesus; Patriota, Yuri Basílio Gomes; Ribeiro, António José; Veiga, Francisco; Hallwass, Fernando; Silva-Filho, Edson Cavalcanti; da Silva, Durcilene Alves; Soares, Monica Felts de La Roca; Wanderley, Almir Gonçalves; Soares-Sobrinho, José Lamartine
Graphical abstract: Highlights: Acetylated cashew gum was eco-friendly synthesized by the new solvent-free method. New NMR spectroscopy methodology for evaluation of degree of substitution was developed. Modified acetylated cashew gum nanoparticles were developed for drug delivery system. Nanoparticles were developed for sustained oral delivery of insulin. Abstract: Cashew gum (CG) is a biopolymer that presents a favorable chemical environment for structural modifications, which leads to more stable and resistant colloidal systems. The gum was subjected to an acetylation reaction using a fast, simple, solvent-free and low cost methodology. The derivative was characterized by infrared and NMR spectroscopy, elemental analysis, coefficient of solubility and zeta potential. The modified biopolymer was used as a platform for drug delivery systems using insulin as a model drug. Nanoparticles were developed through the technique of polyelectrolytic complexation and were characterized by size, surface charge, entrapment efficiency and gastrointestinal release profile. The nanoparticles presented size of 460 nm with a 52.5% efficiency of entrapment of insulin and the electrostatic stabilization was suggested by the zeta potential of + 30.6 mV. Sustained release of insulin was observed for up to 24 h. The results showed that acetylated cashew gum (ACG) presented potential as a vehicle for sustained oral insulin release.